The diagnostic utility of procalcitonin, interleukin-6 and interleukin-8, and hyaluronic acid in the Norwegian consensus definition for early-onset neonatal sepsis (EONS) - Nakstad, Britt (Infect Drug Resist, 2018)
INTRODUCTION: A key challenge in identifying serious bacterial infection in new born infants is the nonspecific clinical presentation of early-onset neonatal sepsis (EONS). Routinely used C-reactive protein, white blood cell count, and platelets are nonspecific. We assessed the diagnostic utility of single biomarkers or combinations of procalcitonin (PCT), interleukin (IL)-6, IL-8, and hyaluronic acid (HA) in newborn infant with EONS, and in human umbilical cord blood (HUCB) from deliveries with chorioamnionitis. MATERIALS AND METHODS: Blood was collected from term infants with strictly defined EONS (group 1, n=15), healthy term infants (group 2, n=15), and the umbilical vein from pregnancies with suspected chorioamnionitis (group 3, n=8), and from healthy pregnancies with no signs of infection (group 4, n=15). RESULTS: Neonatal plasma PCT and IL-8 showed good predictive value (90% and 83%) for EONS, and the combination of IL-6 or HA with PCT increased the predictability to 87% and 90%, respectively. PCT, IL-6, IL-8, and HA were 8.4-, 4.5-, 3.6-, and 1.9-fold higher when compared with plasma levels in noninfected neonates. PCT, IL-6, and IL-8 in HUCB predicted chorioamnionitis and fever in the delivering mother (89%, 83%, and 72%, respectively). HA was a poor predictor (59%), but its predictability increased in combination with PCT, IL-8, or IL-6. In HUCB from chorioamnionitic deliveries, IL-6, IL-8, and PCT were 23-, 14-, and 2.4-fold higher, respectively, when compared with HUCB from healthy deliveries. There was no correlation between C-reactive protein, white blood cell, and platelet count with PCT, IL-6, IL-8, or HA. CONCLUSION: In neonates that fulfilled the Norwegian consensus definition of neonatal sepsis, PCT, IL-6, and IL-8, but not HA, have the potential to improve our management of neonates at risk. Except for PCT and IL-8, both with a predictability of >80% in neonatal plasma, combinations of biomarkers increased the predictability for EONS and chorioamnionitis.